Digital Library Transformation in Supporting Information Literacy in the Era of Artificial Intelligence - Larisu, Zulfiah (PT. Anagata Sembagi Education, 2025)
This study aims to describe the transformation of digital libraries in supporting information literacy in the era of artificial intelligence (AI). The research method used is descriptive qualitative, involving 10 informants consisting of librarians, lecturers, and students as active users of digital libraries. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the Miles & Huberman model through the stages of data reduction, data presentation, and drawing conclusions. The results show that digital libraries have transformed through the application of AI, such as intelligent search systems, chatbots, and automatic source recommendations. This transformation has been proven to support the improvement of user information literacy, especially in the skills of accessing, evaluating, and utilizing academic information. However, challenges that arise include limited infrastructure, resistance from some users, and the need to improve librarians' competencies in mastering AI-based technology. These findings confirm that digital libraries play a vital role in strengthening information literacy in the digital era, while also demanding a sustainable development strategy.